Guillian-Barre syndrome. - Talukder, RK; Sutradhar, SR; Rahman, KM; Uddin, MJ; Akhter, H (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):748-56 The abstract of this article is available on the PubMed website